Adakah Pengaruh Event dalam Economic Calendar terhadap Gold Price (XAU/USD)? - Emilda Emilda (Universitas Indo Global Mandiri)
ABSTRACTThis research is based on phenomena that exist in the world of traders who make events in the economic calendar as one of the fundamental analysis references in making trading decisions. Event data released in the economic calendar are expected to have an impact on the market. This study aims to determine whether there is an influence of the event released in the economic calendar on the gold price (XAU/USD). Data analysis techniques in this study using SPSS, namely IBM Statistics SPSS 24. Data analysis methods in this study are the dependent methods. This study uses monthly event data and the monthly gold price (XAU/USD) for 3 years, namely the period 2017 to 2019. The gold price in this study is the change in the price of spot dollar gold futures (XAU/USD), while the event in this study are events that are estimated to have a high and moderate impact on the price of gold futures (XAU/USD). From five hypotheses in this study, there were three hypotheses that were accepted and two hypotheses that were not accepted. The results in this study, the Federal Funds Rate variable has a positive influence on the price of gold (XAU/USD), the ISM Manufacturing PMI variable, the Unemployment Rate, ADP non – farm employment have negative influence on the price of gold (XAU/USD). Whereas, Average Hourly Earning does not have a significant effect on the price of gold (XAU/USD).Keywords: Event, Economic Calendar, and Gold Price (XAU/USD) ABSTRAKPenelitian ini didasarkan pada fenomena yang ada di dunia pedagang yang membuat peristiwa dalam kalender ekonomi sebagai salah satu referensi analisis fundamental dalam pengambilan keputusan perdagangan. Data acara yang dirilis dalam kalender ekonomi diharapkan berdampak pada pasar. Penelitian ini bertujuan untuk mengetahui apakah ada pengaruh peristiwa yang dirilis dalam kalender ekonomi terhadap harga emas (XAU/USD). Teknik analisis data dalam penelitian ini menggunakan SPSS, yaitu IBM Statistics SPSS 24. Metode analisis data dalam penelitian ini adalah metode dependen. Penelitian ini menggunakan data peristiwa bulanan dan harga emas bulanan (XAU/USD) selama 3 tahun, yaitu periode 2017 hingga 2019. Harga emas dalam penelitian ini adalah perubahan harga emas berjangka spot dolar (XAU/USD), sedangkan event dalam penelitian ini adalah event yang diperkirakan memiliki dampak tinggi dan sedang pada harga emas berjangka (XAU/USD). Dari lima hipotesis dalam penelitian ini, ada tiga hipotesis yang diterima dan dua hipotesis yang tidak diterima. Hasil dalam penelitian ini, variabel Federal Funds Rate memiliki pengaruh positif pada harga emas (XAU/USD), variabel PMI Manufaktur ISM, Unemployment Rate, ADP non-farm employment memilikipengaruh negatif pada harga emas (XAU/USD). Sedangkan, signifikan terhadap harga emas (XAU/USD).Kata Kunci: Peristiwa, Kalender Ekonomi, Harga Emas